ANALYSIS OF MONITORING STUDIES ON AFRICAN SWINE FEVER VIRUS DNA DETECTION CARRIED OUT IN 2017 - D. N. Fedoseyeva; Ye. V. Aronova; A. A. Varentsova; A. A. Yelsukova; Ali Mazloum; D. V. Sharypova; N. N. Vlasova; A. S. Igolkin (Ветеринария сегодня)
The paper describes the results of testing of biomaterial from domestic pigs and wild boars by real-time PCR used for African swine fever virus genome detection, carried out in the FGBI “Federal Centre for Animal Health” (Vladimir). In 2017 8,500 samples from 44 subjects of the Russian Federation were tested within the framework of the state laboratory monitoring. African swine fever virus genome was detected in 504 samples. In 2017 ASF outbreaks were registered in the Urals and Siberian Federal Districts of the RF for the first time. The conducted research and persistent ASF infection in the territory of the RF have demonstrated the need for further surveillance in the populations of susceptible animals. Development, organization and implementation of the program for ASF spread surveillance in wild fauna remains a high priority. It is necessary to create and implement sampling schedules with uniform sampling of biomaterial and submission of the collected samples to the research laboratories for timely ASF outbreak containment at the regional level.